Edukasi Aromaterapi Lemon untuk Mengurangi Emesis gravidarum dan Mencegah Komplikasi Maternal pada Ibu Hamil di Posyandu Pattiro Bajo - Mutmainnah Mutmainnah; St. Malka (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Emesis gravidarum is a common condition during early pregnancy characterized by nausea and vomiting. Although generally physiological, it may progress to hyperEmesis gravidarum if not managed properly. Observations at Pattiro Bajo Integrated Health Post (Posyandu) indicated that most pregnant women lacked knowledge about the use of lemon aromatherapy as a complementary therapy. Method: This community service program aimed to improve pregnant women’s knowledge regarding lemon aromatherapy for managing Emesis gravidarum. A participatory educational approach was implemented through interactive lectures, discussions, and demonstrations involving 10 first- and second-trimester pregnant women. Knowledge was evaluated using pretest and posttest questionnaires. Results: Before the intervention, 60% of participants had moderate knowledge and 40% had poor knowledge. After the education program, all participants (100%) achieved good knowledge. The mean knowledge score increased from 1.40 to 3.00, with an average improvement of 1.60 points, indicating the effectiveness of the educational intervention. Conclusion: Health education on lemon aromatherapy effectively improved pregnant women’s knowledge of the non-pharmacological management of Emesis gravidarum and may support maternal health promotion and the prevention of pregnancy-related complications.